(untitled) (Research, Society and Development, 2021)
The learning of children with ADHD in Elementary School I is presented as the theme of this study. The objective is to analyze scientific studies published between 2016 and 2021, which present contributions on the disorder and on the child’s teaching-learning process in school and family environments. To meet the objective, a qualitative and exploratory research was carried out through a systematic literature review that identified the largest number of results in the Google Scholar Database and after applying the inclusion and exclusion criteria, 21 articles remained for analysis. Among the results found, the constant changes in the name of the disorder stand out, the differences regarding the types of disorder and the perceptions of authors about the existence or not of it, in addition to a reflection on the inclusion or exclusion of children with ADHD. It is considered that the study provided a greater understanding of the disorder and how these children learn, in addition to being relevant to emphasize different methodologies and activities, both in the school and in the family environment.